2006
DOI: 10.1038/sj.leu.2404143
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intensity conditioning allows for up-front allogeneic hematopoietic stem cell transplantation after cytoreductive induction therapy in newly-diagnosed high-risk acute myeloid leukemia

Abstract: There is substantial need to improve the outcome of patients with high-risk acute myeloid leukemia (AML). The clinical trial reported here investigated a new approach of up-front allogeneic hematopoietic stem cell transplantation (HSCT), provided a median of 40 days (range 22-74) after diagnosis, in twenty-six consecutive patients with newly-diagnosed high-risk AML characterized by poor-risk cytogenetics (n ¼ 19) or inadequate blast clearance by induction chemotherapy (IC, n ¼ 7). The median age was 49 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 35 publications
0
38
0
2
Order By: Relevance
“…In a similar approach, the Dresden Group investigated RIC-HSCT performed in aplasia after induction chemotherapy for high-risk AML. 23 In their study, an impressively short median interval of 40 days between diagnosis and transplantation was achieved by an urgent donor search programme of DKMS (the German bone marrow donor registry), one of the largest stem cell Early allogeneic transplantation for complex karyotype AML C Schmid et al donor registries worldwide. However, it took almost 7 years to include 26 high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar approach, the Dresden Group investigated RIC-HSCT performed in aplasia after induction chemotherapy for high-risk AML. 23 In their study, an impressively short median interval of 40 days between diagnosis and transplantation was achieved by an urgent donor search programme of DKMS (the German bone marrow donor registry), one of the largest stem cell Early allogeneic transplantation for complex karyotype AML C Schmid et al donor registries worldwide. However, it took almost 7 years to include 26 high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of this strategy has been shown prospectively, both as initial therapy for patients with high-risk disease and for refractory patients with active disease. 10,11 We have given clofarabine with the intent to reduce disease burden immediately before HCT for AML. Clofarabine has significant activity in relapsed leukemia with low morbidity and mortality in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 This cytoreductive chemotherapy 'bridge' has produced promising results in early studies for patients with newly diagnosed high-risk disease and relapsed patients with active disease. We have employed clofarabine salvage for this purpose and present results from 17 consecutive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 presents the results of 14 relatively recent published experiences of using reduced-intensity conditioning in trials that enrolled at least 15 AML patients. 19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In general, most of the trials were conducted during the periods from 1998 through 2004 but the publications reported heterogeneous patients with respect to disease status at transplant (CR1, CR2, relapse, refractory disease). Further, the reports often differed as to whether the studies were retrospective analyses versus prospective trials.…”
Section: Definitionsmentioning
confidence: 99%